2007
DOI: 10.1080/13557850701616961
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting Low-Income Healthy Women to Research: An Exploratory Study

Abstract: Objective-The study goals were (1) to assess the feasibility of using an existing telephone health information and referral service for low-income, ethnically diverse women to recruit women for research participation; (2) to assess the feasibility of recruiting low-income, African American and Latino men into health research through the women callers to the telephone service; and (3) to describe the challenges women face and the strategies they use when talking to men about the men's health and research partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 54 publications
(59 reference statements)
2
12
0
Order By: Relevance
“…The overall rate of willingness to participate was 50% (95% confidence interval 43%–57%), similar to that for Spanish and English callers in our original pilot test 2 and in the Genetic Counseling component of the study. 3 Of the 200 callers invited to participate, 77 spoke English; other languages spoken were Mandarin (41), Cantonese (21), Vietnamese (55), and Korean (6).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…The overall rate of willingness to participate was 50% (95% confidence interval 43%–57%), similar to that for Spanish and English callers in our original pilot test 2 and in the Genetic Counseling component of the study. 3 Of the 200 callers invited to participate, 77 spoke English; other languages spoken were Mandarin (41), Cantonese (21), Vietnamese (55), and Korean (6).…”
Section: Resultssupporting
confidence: 60%
“…Importantly, we demonstrated in a prior pilot study that approximately 50% of English and Spanish-speaking EWC callers were willing to talk about an entirely new topic when asked to do so by an EWC Information Specialist (IS). 2 …”
mentioning
confidence: 99%
“…When a specific study is noted in the text, we used the specific terminology of the article. Additionally, we found 33 studies that focused exclusively on recruitment and/or retention of women [21][22][23][24][25][26][27][28], and 20% of studies that focused on a specific population group. Although the NIH mandate specifically focused on the recruitment of women for clinical trials, we found no reviews that included information regarding the recruitment numbers of women in prior studies.…”
Section: Descriptive Resultsmentioning
confidence: 96%
“…Specifically, research on the role of women in men's health has included studies on the influence of women on men's dietary behaviors (Allen, Griffith, & Gaines, 2013;Homish & Leonard, 2007), gender roles and relations in health research Joseph, Kaplan, & Pasick, 2007), women's thoughts on the sexual health and sexually transmitted disease testing of men (Oliffe et al, 2013), and women's influence on substance use by their male partners (Homish & Leonard, 2007;Leonard & Homish, 2005;Westmaas, Wild, & Ferrence, 2002). Of the various angles at which the role of women in the lives of men has been examined, the role of female caregivers is presented most frequently in the literature, particularly with regard to the physical health of men.…”
Section: The Current Study Reports Findings From the Black Women's Pementioning
confidence: 99%